Research on Cluster Routing Protocol Based on Genetic Algorithm and Astar Algorithm (Informatica, 2024)
In the routing protocol of wireless sensor networks, power consumption of cluster head nodes and central nodes is too fast, which leads to a short network life cycle. Aiming at the problem that the energy loss of cluster head node and central node is too fast in the clustering routing protocol of wireless sensor networks, a clustering routing protocol based on genetic algorithm and Astar algorithm is proposed. Firstly, in the process of selecting cluster head nodes, the optimal cluster head combination is selected by optimizing the genetic algorithm and improving fitness function, and five other factors, such as the energy level of nodes, the number of times nodes become cluster heads, the distance between cluster heads, the distance between cluster heads and ordinary nodes, and the distance between cluster heads and base stations, are comprehensively considered. Secondly, the Astar algorithm, a heuristic function of node energy and transmission distance, is used to select the path for inter-cluster routing. Finally, the sensor network transmits information.Through the simulation results, it is shown that compared with other protocols, the proposed protocol can effectively reduce the node death rate and balance the overall energy consumption of the network to extend the network lifetime.